Sanctions, Shadow Fleets, and the Erosion of Maritime Governance in Contemporary International Relations - Joseph A. Osazuwa (Goodwood Publishing, 2026)
Purpose: This study examined how sanctions-induced shadow fleet operations undermined maritime transparency, navigational safety, environmental protection, and legal accountability, and assessed how jurisdictional limitations, institutional fragmentation, commercial intermediaries, and geopolitical interests affected enforcement against these networks in contemporary international relations. Research Methodology: The study adopted a qualitative research design based on documentary analysis, drawing on recent scholarly literature, legal instruments, maritime security reports, and relevant cases, including Nigeria's experience with the M/T Heroic Idun, interpreted through Regime Theory. Results: Shadow fleets produced a high level of maritime opacity through reflagging, Automatic Identification System manipulation, shell companies, uncertain insurance, and concealed commercial relationships; jurisdictional limits and overlapping mandates delayed intervention, while brokers, registries, insurers, and charterers diffused liability, and geopolitical disagreements encouraged selective enforcement. Nigeria's surveillance capacity had improved through Falcon Eye and the Deep Blue Project, yet preparedness for sanctions-related investigation and beneficial-ownership tracing remained low to moderate. Conclusions: Shadow fleets exposed structural weaknesses in the international maritime regime and transformed sanctions evasion into a governance, environmental, and security challenge requiring integrated enforcement. Limitations: The qualitative, document-based design restricts generalization and does not capture primary operational or financialintelligence data. Contributions: The study extends Regime Theory to shadow-fleet governance and offers Nigeria-specific policy direction for enforcement reform.